2013
DOI: 10.1192/bjp.bp.112.114074
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of reactive attachment disorder in a deprived population

Abstract: In this deprived general population, RAD was not rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 17 publications
3
74
3
1
Order By: Relevance
“…Our estimated RAD prevalence lies between the prevalence estimate found in a large sample of 6- to 8-year-old, socioeconomically deprived children [51], and the prevalence in severely maltreated toddlers in foster care [52]. Compared to another study on RAD using DAWBA in high-risk foster youths [29], our estimate was quite moderate.…”
Section: Discussionmentioning
confidence: 54%
“…Our estimated RAD prevalence lies between the prevalence estimate found in a large sample of 6- to 8-year-old, socioeconomically deprived children [51], and the prevalence in severely maltreated toddlers in foster care [52]. Compared to another study on RAD using DAWBA in high-risk foster youths [29], our estimate was quite moderate.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies (Kay & Green, 2013;Selwyn et al, 2014) found a high rate of attachment disorder in similar samples, and Minnis et al (2013) estimated the prevalence in a deprived population as lying in the range of .94-2.10. This is a disorder with very different prevalence rates according to how broadly the criteria are defined (Meltzer, Gatward, Corbin, Goodman, & Ford, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…The disinhibited form is known to be associated with significant psychiatric morbidity [13] and can persist despite changes in caregiving context [14]. Inhibited RAD is thought to be very rare beyond the specific context of maltreatment [14] but we have recently shown that the disinhibited form is far from being rare and has a prevalence of around 1.4% in a deprived population [15]—similar to or even higher than the population prevalence of ASD [16]. We have also found that children with RAD often have complex neurodevelopmental problems [17] and that, even after living for several years in loving adoptive families, these children can still have problems that are a major burden for themselves, their families, and their peers [18].…”
Section: What Are the Maltreatment-associated Psychiatric Problems?mentioning
confidence: 99%